EVEPRIM: Recursos Educativos Abiertos para la Enseñanza de la Matemática en la Educación Primaria de Costa Rica - Meza-Cascante , Luis Gerardo (2025)
Under the generic name of the EVEPRIM Project (Virtual Education for Primary Students), the School of Mathematics at the Costa Rica Institute of Technology (ITCR) has developed a series of extension projects (EVEPRIM 6, EVEPRIM 3, EVEPRIM 3.1, EVEPRIM 3.2, and EVEPRIM 6.1) focused on creating Open Educational Resources (OER) to strengthen mathematics teaching in Costa Rican primary education. Through digital materials, educational videos, and interactive applications, EVEPRIM aims to improve mathematical learning and promote equitable access to high-quality resources. This article provides a contextualization of the project and presents the main results obtained to date.